1996
DOI: 10.1051/radiopro/1996007
|View full text |Cite
|
Sign up to set email alerts
|

Transferts du radiocobalt en milieu terrestre

Abstract: Caractéristiques générales du cobaltLe cobalt, de numéro atomique Z = 27, est un élément de transition qui possède une masse atomique de 58,9. Dix isotopes radioactifs (54 à 64) et cinq isomères nucléaires sont connus. Le plus important d'entre eux, en radioécolo-gie terrestre, est le cobalt 60 (émetteur gamma, période : 5,26 ans) qui appartient au groupe 2 (radiotoxicité forte).D'un point de vue chimique le cobalt possède deux valences principales (II et III), le degré II étant le plus stable, mais il peut êt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…7 that most of 60 Co was mainly associated with Mn oxides (easily reducible phase). These results corroborate the findings of Colle et al (1996) that had also observed the relationship between this radionuclide and the manganese oxides. No significant fraction of 60 Co was observed in the bioavailable phase for Nitisol, while this phase represents 56% of total 60 Co present in FerralsolFe and 36% in the Acrisol.…”
Section: Co Tf Valuessupporting
confidence: 95%
“…7 that most of 60 Co was mainly associated with Mn oxides (easily reducible phase). These results corroborate the findings of Colle et al (1996) that had also observed the relationship between this radionuclide and the manganese oxides. No significant fraction of 60 Co was observed in the bioavailable phase for Nitisol, while this phase represents 56% of total 60 Co present in FerralsolFe and 36% in the Acrisol.…”
Section: Co Tf Valuessupporting
confidence: 95%
“…According to these results, 14% of added 60 Co is readily bioavailable and 60% is associated to oxidizable compounds. Despite the very low content of Mn oxides in the Histosol (Table 2), about 18% of added 60 Co was associated with the easily reduced phase indicating the great affinity between 60 Co and Mn oxides, also observed by Rosa (2006) and Colle et al (1996).…”
Section: Geochemical Partitioning Of 60 Comentioning
confidence: 49%
“…6). According to Colle et al (1996) a large percentage of the 60 Co in soils is found associated to manganese oxides; thus a bigger mobility of 60 Co is expected in reducing environment as, for instance, flooded soils. In the case of Ferralsols, this association with easily reducible compounds could be considered as a very stable association, once flooding is rare under its natural conditions, thanks to its physical properties and very deep profiles that guarantee a good drainage.…”
Section: Geochemical Partitioning Of 60 Comentioning
confidence: 99%
“…Or also pH, which modifies the charges of Fe and Mn oxides and indirectly can affect the CEC of a soil. The presence of nutrients can also affect the uptake of cobalt by plants and one of the possible explanations is that they compete with Co for the soil components's sorption sites [18]. In their work, Bartoly et al [32] noted that in Brazilian Nitisols the transfer of 60 Co to plants is lower compared to Ferralsols and Acrisols and suggested that Nitisol is the most fertile soil of the three (higher values of CEC and higher levels of P, K and Ca), and thus may explain this disparity.…”
Section: Reviewed Articles Withmentioning
confidence: 99%
“…Although these releases are controlled and follow specific standards, they contribute to the inventory of radionuclides in the ecosystem [16,17]. According to Colle, Debet, and Real [18], radiocobalt did not significantly contaminate terrestrial environments due to its absence in atmospheric effluents from power plants and in the fallout from nuclear weapons testing. Moreover, the radiocobalt released from the Chernobyl accident was restricted to its vicinity.…”
Section: Introductionmentioning
confidence: 99%